Dysregulated serum chloride and clinical outcomes in critically ill adults: A systematic review and meta-analysis - Xiaoliang Wan; Feiyao Deng; Xue Bai; Chenxi Xiang; Chuan Xu; Linxiao Qiu (PLoS ONE, 2025)
Dysregulated serum chloride levels are prevalent in critically ill patients. However, their clinical impact remains unclear. This first systematic review and meta-analysis quantified the prevalence of hypochloremia and hyperchloremia, and their associations with mortality and acute kidney injury (AKI) in critically ill populations. We searched PubMed, Embase, Web of Science, and the Cochrane Library for studies reporting hyperchloremia prevalence or outcomes in adult ICU patients until August 2025. Statistical analyses were conducted using Stata v16.0, and study quality was assessed using the Newcastle-Ottawa Scale. 34 studies (n = 175,021 patients) were included. The aggregated prevalence of hyperchloremia was 34% (95% CI [26%−43%]) and hypochloremia was 14% (95% CI [1%−28%]). Meta-analysis demonstrated that both hyperchloremia and hypochloremia were significantly associated with increased mortality, conferring a 28% (OR = 1.28, 95% CI [1.08–1.52]) and 55% (OR = 1.55%, 95% CI [1.33–1.81]) elevated risk for mortality, respectively. Crucially, a dose-response analysis revealed a non-linear relationship between serum chloride levels and mortality, confirming that the risk is independently elevated at both extremes. Furthermore, hyperchloremia was linked to an increased risk of AKI (OR = 1.40, 95% CI [1.07–1.85]). These findings establish dysregulated serum chloride as a common and clinically significant biomarker, underscoring the necessity of monitoring and managing both high and low chloride levels in critically ill patients. Future large-scale studies are warranted to validate these results and elucidate the mechanistic pathways linking chloride dysregulation to such adverse outcomes.